STUDI PENYUSUNAN PROFIL DAERAH IRIGASI JAMBO REUHAT - Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2016)
The purpose of compilation study of Jambo Reuhat irrigation area profile was to collect correct and actual data and information as input in planning P3A organizational empowerment/”Keujruen Blang” program to improve the management of participatory irrigation in Jambo Reuhat Irrigation Area based on potential local resources. Jambo Reuhat Irrigation Area is located in the administrative area of East Aceh Regency which includes Idi Rayeuk, Idi Tunong, Darul Ihsan and Banda Alam Sub-districts. The method used was descriptive research which is case study and field study. SWOT analysis was performed to formulate strategy and policy which would be used. This study also distributed questionnaires to 12 (twelve) P3A in Jambo Reuhat Irrigation Area. The socio-economic aspect in Jambo Reuhat Irrigation Area should increase business opportunity for productive economy which could be developed optimally by agricultural intensification, improving technology mastery pre- and post-harvest, agronomy and agricultural business diversification. In organizational aspect, the status of P3A/”Keujruen Blang” should be raised to legal entity and have legality in performing works related to improving the performance of Jambo Reuhat Irrigation Area. In technical aspect, damaged irrigation channels and buildings with decreased functions should be. In agricultural business aspect, mastery and application method of efficient technology in crop processing, crop preparation to post-harvest should be improved. Potential local resource which should be developed was animal farming to support agricultural activities and to be integrated optimally with activities to improve farmers’ economy.